Intervensi Pasca Trauma pada Anak Korban Kekerasan Seksual di Indonesia - Mu’min, Sitti Aisyah; Santri, Dewi; Susilowati, Tasya (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2023)
Violence against children is an intentional act that causes emotional and physical harm. Recovery and services for child victims of sexual violence often focus on legal and health interventions, neglecting social and psychosocial recovery. This research analyzes the form of intervention for child victims of sexual violence in Kendari's official institutions. It employs a qualitative descriptive method, emphasizing the natural character of the data without using calculations. The research reveals a high and increasing incidence of child sexual violence in Kendari, affecting all sub-districts. In response, the Kendari city government has issued regional regulations to protect children. The research highlights the need for psychosocial interventions for traumatized children. These interventions include: 1) Psychosocial Assistance, addressing the psychological and social conditions of affected children; 2) Counseling and Therapy, providing immediate attention to prevent worsening psychological burdens; 3) Support by UPTP2A Kendari, helping children resume their activities after receiving psychosocial services, counseling, and therapy.